Library management skills of private higher education institution (hei) librarians in La Union / Arnel T. Valdez. - Valdez, Arnel T. (Saint Louis College : [s.n.], 2018)
This study assessed the library management skills of librarians in private Higher Education Institutions (HEls) in La Union. Specifically, it looked into the level of manifestation of the library management skills of librarians along leadership, people, budgeting and finance, quality service, information and technology, and technical skills; and strengths and weaknesses of the librarians along the foregoing skills. A three-year library management skills strategic plan (2018-2022) was formulated and validated to address the findings of the study. The descriptive method of research was employed using the 16 Vice President for Academic Affairs (VAA's) / Administrators and the 27 Librarians and Staff of the selected HEI's in La Union as respondents. Data were gathered using the questionnaire checklist, tabulated and analyzed using the weighted means. The study found that the level of manifestation of the library management skills of the librarians in private HEIs in La Union was high. The librarians had all the library management skills as their strengths. The three-year library management skills strategic plan was very highly valid. It was concluded that the librarians in the private HEIs of La Union are capable in discharging their library management functions. The librarians in the private HEIs in La Union are effective in managing their libraries. The three-year strategic plan is an essential tool to heighten and sustain the management skills of librarians.
Bibliography: pages 61-63.
CHED-La Union
Keywords: Avademic libraries -- Administration